Role of Critical Reflection in Practicum of Pre-service Teacher Education - Chauhan, Sonika (JOURNAL OF INDIAN EDUCATION, 2015)
This paper is an attempt to enhance the perspective of reflection in the discourse of teacher education. The study tries to look at the notion of critical reflection as a possible source of pedagogical knowledge in the pre-service teacher education programme. Through this paper an attempt has been made to understand how student teachers’ critical awareness of themselves and their beliefs lead to the development of personal and professional knowledge. The data for the study was obtained from the teaching experiences of student teachers of the Bachelor of Education (B.Ed) programme. The participants were six student teachers doing their practice teaching in a central school of Delhi. It was observed that student teachers come to teacher education program with a set of beliefs and preconceptions about teaching-learning process as well as of learners based on their own experiences as student. It was also found that through dialogue and guided practice student teachers can examine their and others’ pedagogical practice as critical. The findings of the study could help in making the school experience programme more comprehensive and meaningful for the student teachers.